Are white-rot fungi a real biotechnological option for the improvement of environmental health? - Tortella, G.; Durán, N.; Rubilar, O.; Parada, M.; Diez, M. C. (Critical reviews in biotechnology, 2015)
Abstract The use of white-rot fungi as a biotechnological tool for cleaning the environment of recalcitrant pollutants has been under evaluation for several years. However, it is still not possible to find sufficiently detailed investigations of this subject to conclude that these fungi can decontaminate the environment. In the present review, we have summarized and discussed evidence about the potential of white-rot fungi to degrade such pollutants as polycyclic aromatic hydrocarbons, dyes or antibiotics as an example of the complex structures that these microorganisms can attack. This review also discusses field experiment results and limitations of white-rot fungi trials from contaminated sites. Moreover, the use of catabolic potential of white-rot fungi in biopurification systems (biobeds) is also discussed. The current status and future perspectives of white-rot fungi, as a viable biotechnological alternative for improvement of environmental health are noted.